Social Work, Political Violence and Historical Change: Reflections from Northern Ireland - Jim Campbell (Social Work and Society)
In this paper the author outlines the background to the history of the conflict in Northern Ireland which led to the current "˜Troubles'. In this discussion a range of key ideas are highlighted, including the nature of sectarianism and patterns of violence which have profoundly affected the society. The second part of the paper reviews a number of issues which face social workers when they try to deal with the effects of such violence as well as highlighting new challenges which have emerged as the society moves towards the resolution of conflict. It concludes with the argument that, wherever there is such conflict in the world, social workers need critically to understand the way in which political and social structures impinge upon their everyday practice.